Trade Openness and Poverty Reduction in South Africa - Glenda Maluleke; Nomfundo Vacu-Nqila (Acta Economica)
The study examined the impact of trade openness on poverty rate in South Africa. The ARDL bounds testing approach was used with annual data covering the period from 1990 to 2021. The study estimated four models, that is, an income-based model and a consumption-based model using two measures of trade openness which are total trade and exports as a percentage of GDP. For the income-based model 1, the findings confirmed that trade openness has a long-run negative impact on the poverty rate, while it has no significant impact in the short run. For model 3, it was found to be insignificant in the long run while in the short run, it was found that exports lead to a decrease in poverty rates. The finding confirmed that for the consumption-based model 2, trade openness leads to a decrease in the poverty rate in the long and short run. For model 4, in which exports are used as a measure for trade openness, it was found that it leads to a decrease in household consumption in the long run. Based on the results the study recommends that governments in developing countries should engage with other countries to increase their export capacity and in turn reduce their respective poverty levels.